1989
DOI: 10.1590/s0006-87051989000200001
|View full text |Cite
|
Sign up to set email alerts
|

Fenóis, peroxidase e polifenoloxidase na resistência do cafeeiro a Meloidogyne incognita

Abstract: Plântulas dos cultivares Mundo Novo, de Coffea arabica, suscetível, e Apoatã, de Coffea canephora, resistente, foram inoculadas com ovos de Meloidogyne incognita raça 2, e avaliadas em duas fases do ciclo de desenvolvimento do parasito, isto é, na de penetração de larvas e na de fêmeas com ovos. Não foram observadas diferenças quanto ao desenvolvimento radicular e da parte aérea entre plântulas inoculadas e não inoculadas, nas duas avaliações. Nos dois cultivares, houve aumento no teor de fenóis nas plântulas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, in the current study, the role played by TSP was not clearly involved in the increased resistance to M. exigua of coffee plants from both cultivars supplied with Si, even considering that their fungitoxic effects, especially those of the most oxidated ones, including the lignin precursors, can affect nematode colonization and reproduction on roots. Mazzafera et al. (1989) found no difference in the content of phenolic compounds on roots of coffee plants from cvs Mundo Novo and Apoatã IAC 2258, susceptible and resistant, respectively, to M. incognita , even though coffee plants have high contents of phenolics in their roots and leaves.…”
Section: Discussionmentioning
confidence: 69%
“…However, in the current study, the role played by TSP was not clearly involved in the increased resistance to M. exigua of coffee plants from both cultivars supplied with Si, even considering that their fungitoxic effects, especially those of the most oxidated ones, including the lignin precursors, can affect nematode colonization and reproduction on roots. Mazzafera et al. (1989) found no difference in the content of phenolic compounds on roots of coffee plants from cvs Mundo Novo and Apoatã IAC 2258, susceptible and resistant, respectively, to M. incognita , even though coffee plants have high contents of phenolics in their roots and leaves.…”
Section: Discussionmentioning
confidence: 69%
“…Also, lower levels of fertilization with potassium source, generally results in an increase of alkaloids percentage in plants . Mazzafera , when studying the effect of nutrients supplement on the content of caffeine in coffee leaves (Arabian Coffea L.), observed that the decrease of potassium fertilization induced an increase in the content of caffeine in leaves.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, however, results can vary depending on the nitrogen source used in the fertilization (nitrate, ammonia or urea) (39). According to Mazzafera (40), as alkaloids are nitrogen compounds, low amounts of caffeine are expected to occur in treatments with limited availability of nitrogen. The caffeine level varies as an integrated part of nitrogen compounds metabolism in the plant as a function of availability of this element.…”
Section: Effect Of Fertilization Type On the Performance Of Co 2 Extr...mentioning
confidence: 99%
“…This is because plant defense response to nematodes include the activation of the metabolic pathways involved in phytoalexin biosynthesis, an increase in the activity of enzymes such as phenylalanine ammonia-lyase, deposition of callose and/or lignin and the accumulation of phenolic compounds, peroxidase, polyphenol oxidase, superoxide dismutase, chitinases and proteinase inhibitors (Mazzafera et al, 1989;Salgado and Silva, 2005).…”
Section: Introductionmentioning
confidence: 99%